Rendimientos de maíz regadío : II. diagnóstico foliar en el suelo aluvial de Mendoza (Argentina) - Nijensohn, León (1999)
In a fertilizer assay of irrigated corn on an alluvial soil of ca. 60 cm deep over a stony subsoil (pebbles, gravel, etc.) we look advantage of the great variability among replicates of the same treatments in order lo establish relationships between foliar composition and grain and stubble yields. The main conclusions we arrived at were: 1- N leaf content was the most significant index related to yield. A threshold of 20 g N % for grain and stubble yields above 14 t/ha and 25 t/ha, respectively, was established. 2- Single regressions were also found with P and Zn, but none of the multiple regressions which included N and P with Zn and K were better than the one with N as the sole variable. 3- Although K as a single variable in the regression equation vs. yield had no statistical signification, a threshold of 1.6 9 K % evidenced for grain yields above 16 t/ha. 4- Foliar compositions related to the maximum observed yield (21 t/ha grain and 31 t/ha stubble dry matter) compared with the minimum one (4.1 t/ha grain and 8.1 t/ha stubble) are respectively the following: N 2.54-097 9 %; P 0226-0.152 9 %; K 1.76-1 .48 9 % ; Ca 0.54-039 9 %; Mg 0.16-0.16 9 %; Fe 158-109 mg/kg; Zn 52-24 mg/kg; Mn 88-27 mg/kg and Cu 17-5 mg/kg.